2017
DOI: 10.2140/involve.2017.10.263
|View full text |Cite
|
Sign up to set email alerts
|

Peak sets of classical Coxeter groups

Abstract: We say a permutation π = π1π2 · · · πn in the symmetric group Sn has a peak at index i if πi−1 < πi > πi+1 and we let P (π) = {i ∈ {1, 2, . . . , n} | i is a peak of π}. Given a set S of positive integers, we let P (S; n) denote the subset of Sn consisting of all permutations π, where P (π) = S. In 2013, Billey, Burdzy, and Sagan proved |P (S; n)| = p(n)2 n−|S|−1 , where p(n) is a polynomial of degree max(S) − 1. In 2014, CastroVelez et al. considered the Coxeter group of type Bn as the group of signed permuta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…One of their foundational results established that for an n-admissible set S |P S (n)| = p S (n)2 n−|S|−1 (1) where p S (x) is a polynomial depending on S, which they called the peak polynomial of S. It was shown that p S (x) has degree max(S) − 1, and that p S (x) takes on integral values when evaluated at integers [3, Theorem 1.1]. Similar observations were made for peak polynomials in other classical Coxeter groups (see the work of Castro-Velez, Diaz-Lopez, Orellana, Pastrana [9] and Diaz-Lopez, Harris, Insko, and Perez-Lavin [10]). Using the method of finite differences, Billey, Burdzy, and Sagan gave closed formulas for the peak polynomials p S (x) in various special cases.…”
Section: Introductionmentioning
confidence: 63%
“…One of their foundational results established that for an n-admissible set S |P S (n)| = p S (n)2 n−|S|−1 (1) where p S (x) is a polynomial depending on S, which they called the peak polynomial of S. It was shown that p S (x) has degree max(S) − 1, and that p S (x) takes on integral values when evaluated at integers [3, Theorem 1.1]. Similar observations were made for peak polynomials in other classical Coxeter groups (see the work of Castro-Velez, Diaz-Lopez, Orellana, Pastrana [9] and Diaz-Lopez, Harris, Insko, and Perez-Lavin [10]). Using the method of finite differences, Billey, Burdzy, and Sagan gave closed formulas for the peak polynomials p S (x) in various special cases.…”
Section: Introductionmentioning
confidence: 63%
“…Shortly thereafter, their results were extended to permutations in type B by Castro-Velez et al [2] where it was shown that the number of permutations with a given peak set I is 2 2n−|I|−1 p(n), with p(n) the same as in [1] above. The second author and various collaborators went further by extending these results to types C and D [7], using peaks to study properties of the descent polynomial [6], and then initiating the study of peaks in the context of graphs [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we study the Hamming metric, which measures the number of indices at which two permutations differ and the ℓ ∞ -metric, which measures the maximum componentwise difference between two permutations. Motivated by a paper that studies these metrics on sets of permutations with a given peak set [5], the main purpose of this article is to find the maximum Hamming and ℓ ∞ -metric when restricting to permutations that share a descent set-subsets of the form D(S; n) ⊂ S n for S ⊂ [n − 1]. Theorem 3.2 provides a complete characterization of the maximum Hamming metric on all sets D(S; n) and Theorems 4.1 and 4.2 provide the maximum ℓ ∞ -metric on D(S; n) for particular cases of S. Finding the maximum ℓ ∞ -metric on most sets D(S; n) is still an open problem.…”
Section: Introductionmentioning
confidence: 99%